Efisiensi Teknis Unit Penangkapan Bottom gillnet di Pelabuhan Perikanan Nusantara (PPN) Sungailiat - Afridanelly, Tuti; ., Fauziyah; Agustriani, Fitri (UNIVERSITAS SRIWIJAYA, 2011)
Bottom Gillnet is one of fishing unit used to the advantage of resource demersal fishes.This examination in order to know useful of input(trip, GT ship, BBM, ABK, and the long of net size that used) and output(production) suitable until got maximal productivity technically. This examination was accomplished on November- December 2009 in Nusantara Fishery Port Sungailiat used interview method, cluster analysis, discriminate, and scoring. According to result of cluster analysis got 2 groups of Bottom Gillnet fishing unit consists of group 1 n 2. Group 1 divided by 1A, 1B, and 1C. The result of discriminate showed factor which has influence in forming the group is size of dimention ship (GT), amount of ABK and long of of net was used. Ship Bottom Gillnet which efficient technically those were, first KM Ratulangi with score 3,082, second KM Lingga with score 2,904, and third KM Pusara with score 2,774. The specification of efisien ship was were fishing trip 32 times in a year, the size of ship dimention 4-6 GT, the using of solar 150-210 liter/trip, used ABK 3-4 humans and long of net which used 45-50 pieces. Keywords : Bottom Gillnet, Efficiency, Nusantara Fishery Port Sungailiat. ABSTRAK Bottom Gillnet adalah salah satu alat tangkap yang digunakan untuk pemanfaatan sumberdaya ikan demersal di Pelabuhan Perikanan Nusantara Sungailiat.Penelitian ini bertujuan mengetahui penggunaan input (trip, GT kapal, BBM, ABK dan panjang ukuran jaring yang digunakan) dan output (produksi) yang sesuai sehingga dapat menghasilkan produktivitas yang optimum secara teknis. Penelitian ini dilaksanakan pada bulan NovemberÃ¢â‚¬â€œDesember 2009 di Pelabuhan Perikanan Nusantara (PPN) Sungailiat dengan menggunakan metode wawancara dan analisis cluster, diskriminan serta skoring. Berdasarkan hasil analisis cluster terdapat 2 kelompok unit penangkapan bottom gillnet yaitu kelompok 1 dan 2. Kelompok 1 terbagi menjadi 1A, 1B dan 1C. Hasil diskriminan menunjukan faktor yang berpengaruh dalam pembentukan kelompok adalah ukuran dimensi kapal, (GT), jumlah ABK dan panjang jaring yang digunakan. Kapal bottom gillnet yang efisien secara teknis yaitu pertama KM Ratulangi dengan skorÃ‚Â 3,082, kedua KM Lingga 2,904 dan ketiga KM Pusaka skor 2,774. Kata kunci : Bottom gillnet, Efisiensi, Pelabuhan Perikanan Nusantara Sungailiat